(untitled) (Journal of Engineering, 2011)
An experimental and theoretical analysis was conducted for simulation of open circuit cross flow heat exchanger dynamics during flow reduction transient in their secondary loops. Finite difference mathematical model was prepared to cover the heat transfer mechanism between the hot water in the primary circuit and the cold water in the secondary circuit during transient course. This model takes under consideration the effect of water heat up in the secondary circuit due to step reduction of its flow on the physical and thermal properties linked to the parameters that are used for calculation of heat transfer coefficients on both sides of their tubes. Computer program was prepared for calculation purposes which cover all the variables that affect such type of transient mechanisms. The effect of the power density in the primary circuit and the water flow reduction percentage on the average temperature build up of the water in the primary circuit was investigated. The elapsed time required for the primary circuit average temperature to reach a steady state value was also calculated. These calculations were supported with experimental measurements conducted on a standard cross flow heat exchanger apparatus. The experimental results were compared with the theoretical results for certain power density value at different flow reduction percentages which show a reliable agreement. This relative agreement was necessary to consider the mathematical model with certain assurance for calculating transient parameters for higher power densities that are out of apparatus ranges. The results proved that water average temperature build up in the primary circuit has sharp tendency when the percentage of flow reduction in the secondary circuit reach 25% of its nominal values.